The Routledge handbook of 1989 and the great transformation - Johnston, Rosamund; Panagiotidis, Jannis; Baran-Szołtys, Magdalena; Calori, Anna; Nguyen Vu, Thuc Linh; Peng, Sheng; Schacht, Anastassiya; Ther, Philipp (Routledge, Taylor & Francis Group, 2026)
This cutting-edge collection of essays analyzes the pivotal year of 1989 and the transformation processes that resulted from a historical perspective. It takes the events of that momentous year as a pivot to explore longer-term processes of economic, social, political, and cultural transformation linked to the rise of neoliberalism and globalization since the 1970s and enduring until now.
Enthält Literaturangaben und ein Register
Keywords: Aufsatzsammlung; Geschichte 1970-2025; Globalisierung; Neoliberalismus; Kulturwandel; Wirtschaftsentwicklung; Sozialer Wandel; Politischer Wandel; Ostmitteleuropa; Osteuropa